Pioneers in Forensic Science : Innovations and Issues in Practice - Pyrek, Kelly M. (Boca Raton, FL : CRC Press, 2017)
"This book highlights the contributions of leading forensic science practitioners, iconic figures who have been integral in both establishing current scientific and medicolegal practices and innovative evidence collection, testing, and analysis methods. Such professionals include Henry Lee, Michael Baden, William Bass, Jay Siegel, John Butler, Cyril Wecht, Vincent Di Maio, Marcella Fierro, Barry Fisher, and more. Previously unpublished interviews with these pioneers in the field, expressly undertaken for the purposes this book, examine the last 30 years--past trends that have shaped the field--as well as current and emerging trends that have, and will shape, the future of forensic science."--Provided by publisher.
Chapter 1 The Forensic Science Experts: Pioneers, Masters, and Students -- chapter 2 Flaws and Fraud: The Accusations against Forensic Science -- chapter 3 Quality Improvement in Forensic Laboratories -- chapter 4 Quality Improvement in Forensic Medicine Facilities -- chapter 5 Celebrity and the Forensic Scientist -- chapter 6 The Future of Forensic Science.
OCLC-licensed vendor bibliographic record.
Keywords: LAW -- Criminal Law -- General; Forensic sciences